Cool to be kind : how to negotiate the world of friendships and relationships - Bates, Liz; Dodds, Nigel (Archaeological illustrator) (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Coco, Otto, Ollie, and Ling negotiate the sometimes tricky world of friendships and relationships, observing the unkindness of some and using kindness to change the lives of others.
OCLC-licensed vendor bibliographic record.
Keywords: Friendship -- Pictorial works -- Juvenile fiction; Kindness -- Pictorial works -- Juvenile fiction; EDUCATION / General